y = 4x/3 - 2/3
2006-11-30 10:19:57
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
General slope-intercept form of a linear equation is as follows:
y = mx + b
Therefore, divide through by 3:
3y/3 = 4x/3 - 2/3
ANSWER: y = (4/3)x - 2/3
Where m=4/3 is the slope, b = -2/3 is the y-intercept,
since y = -2/3 when x=0.
2006-11-30 18:21:36
·
answer #2
·
answered by Action 4
·
0⤊
0⤋
The standard slope-intercept form is y = mx + b. So all you have to do to get this into slope-intercept form is divide everything by 3. Then you get:
3y/3 = 4x/3 - 2/3, which simplifies to:
y = (4/3)x - 2/3.
2006-11-30 18:21:00
·
answer #3
·
answered by Amy F 5
·
0⤊
0⤋
Slope intercept form is y = mx + b
So, just divide everything by 3
y = 4/3 x -2/3
2006-11-30 18:39:49
·
answer #4
·
answered by Krisie 2
·
0⤊
0⤋
slope intercept form: (y = mx + b)
y = (4/3)x - 2/3
slope is 4/3
intercept is -2/3
intercept is where x=0
slope is (very important in economics anyway) the rate of change in y for every change in x.
2006-11-30 18:23:29
·
answer #5
·
answered by Brett T 3
·
0⤊
0⤋
Needs to be in the form y = mx + b
Divide both sides by 3 to eliminate the coefficient of y, leaving you with:
y = 4/3 x - 2/3
2006-11-30 18:20:24
·
answer #6
·
answered by Matt 2
·
0⤊
0⤋
y= 4/3 x- 2/3 (y=mx+b)
2006-11-30 18:26:32
·
answer #7
·
answered by rocker 3
·
0⤊
0⤋
it is already in slope intercept form... i'm in 8th grade and we are doing that in math now!!!
2006-11-30 18:26:38
·
answer #8
·
answered by ILY 1
·
0⤊
0⤋
y=(4x-2)/3
2006-11-30 18:20:25
·
answer #9
·
answered by pzratnog 3
·
0⤊
1⤋
y=mx+b
so yes it is
2006-11-30 18:19:27
·
answer #10
·
answered by Gucci_xoxo 2
·
0⤊
0⤋